Whole Foods Market : a CEO's public opinion at odds with a key demographic - Imtiaz, Tahir; Ji, Jing; Mitchell, Andrew; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In August of 2009, the founder and CEO of the successful natural and organic food company Whole Foods Market published an op-ed in the Wall Street Journal espousing a position on the highly contested national health care debate that many perceived to be at odds with the companys core customers. In the midst of a slow news month, the media seized on the apparent contradiction, and many diverse interests used the ensuing attention to further their own agendas.
Originally published: Imtiaz, T., Ji, J., Mitchel, A., & ORourke, J. S. (2010). Whole Foods Market: A CEOs public opinion at odds with a key demographic. 10-01. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Whole Foods Market -- Public opinion; Grocery trade -- Public relations -- United States; Business and politics -- United States